2022
DOI: 10.14740/cr1442
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-Induced Cardiotoxicity in Breast Cancer Patients: A Five-Year Retrospective Study in 10 Centers

Abstract: Background: Cardiotoxicity as a result of anthracycline chemotherapy has been linked to increased morbidity and mortality in breast cancer patients. There is a need for early detection through risk factor identification. To date, no large multicenter study has been conducted to describe the incidence, risk factors and clinical and demographic profiles of breast cancer patients with anthracycline-induced cardiotoxicity (AIC) in the Philippines.Methods: This was a nationwide multicenter retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated a higher risk of CTRCD among women who have hypertension when receiving treatment with potentially cardiotoxic treatment for breast cancer when compared to women who do not have hypertension. [6][7][8] What has not been fully characterized are the risk factors for hypertension, beyond cardiotoxic treatment. Studies in women without breast cancer have identified risk factors for hypertension to include family history, obesity, and older age.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated a higher risk of CTRCD among women who have hypertension when receiving treatment with potentially cardiotoxic treatment for breast cancer when compared to women who do not have hypertension. [6][7][8] What has not been fully characterized are the risk factors for hypertension, beyond cardiotoxic treatment. Studies in women without breast cancer have identified risk factors for hypertension to include family history, obesity, and older age.…”
Section: Introductionmentioning
confidence: 99%
“…Some risk factors associated with anthracycline-induced cardiotoxicity include cumulative dose, female sex, and pre-existing heart conditions such as arterial hypertension [3]. About 10% of breast cancer patients undergoing anthracycline chemotherapy develop cardiotoxicity and about 20% of long-term lymphoma survivors treated with anthracyclines have asymptomatic cardiac dysfunction [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of over 43,000 patients with breast cancer, followed over a median of 53 months, anthracycline chemotherapy was associated with an adjusted hazard risk of 1.26 for the development of heart failure (HF) in women aged 66 -70 years [4]. On the other hand, after cancer therapy, the St. Jude Lifetime Cohort Study showed that the prevalence of cardiac dysfunction, defined by decreased GLS, was 31.8% at a median interval of 23 years from diagnosis in long-term adult survivors of childhood cancers treated with anthracyclines, chest radiation, or both [2].…”
Section: Introductionmentioning
confidence: 99%